Reflections on the new institutional economy and the performance of public organizations - Briseño Ramírez, Hugo; Sánchez Bernal, Antonio (Cooperativismo & Desarrollo, 2019)
The central question that this article intends to answer is: What are the factors that explain the performance of public organizations? Since there are incentive structures and various actors, this question will be addressed from the perspective of the new institutional economy. It is proposed that the management of these entities is influenced by government resources and the order of government responsible for them —principally—; contextual incentives —shortage of the managed resource— and political —competitiveness—; as well as the opportunism with which the organism can act, moving away from the objectives for which it was created. The authors propose that the main agent's perspective, within the framework of the new institutional economy, is a relevant lens with which to assess the work of public bodies. Government organizations will achieve the objectives for which they were created to the extent that the principal has the resources to promote the corresponding actions to do so; count on both contextual and political incentives that drive them to carry out these actions; and the agent directs their efforts to the purpose of their creation and does not deviate from opportunism.
Keywords: organizational performance; public organizations; main-agent perspective; new institutional economy